Code-Switching and Grammar: A Bibliometric Analysis on How Bilingual Students Use English Syntax in Writing - Ravago, Shaira Mae; Quijano, Vincent Jelo F.; Santos, Joseline M. (Future Science / FSH-PH Publications, 2025)
This study investigates how bilingual students employ English syntax in writing through the lens of code-switching. A bibliometric analysis was conducted using Scopus-indexed articles from 2013 to 2023, employing tools like VOSviewer and NVivo to map trends and themes. Results indicate that code-switching enhances grammatical development by fostering metalinguistic awareness, cognitive flexibility, and rhetorical strategy, though concerns remain about its impact on adherence to standard grammar norms in academic writing. Four major thematic clusters were identified: translanguaging pedagogy, biliteracy development, sociocultural identity, and discourse-based grammar instruction. The findings can inform educators and curriculum developers on the syntactic challenges and patterns in bilingual writing and act upon it through authorships of school’s language teaching policies. This is the first bibliometric study to systematically examine the intersection of code-switching and English grammar in the academic writing of bilingual students, offering both theoretical and pedagogical contributions to multilingual education.